Proceso de atención de enfermería en paciente de 25 años, de edad con tuberculosis pulmonar. - Álvarez Duran, Ronaldo Aldair (2020)
The purpose of the clinical case presented below is to treat Pulmonary Tuberculosis, taking into account that in recent years it has become one of the most worrisome diseases in public health and one of the leading causes of mortality at the level world, where one of the civil and political rights is the right to life and personal integrity. In this work, detailed information is found on the humble 25-year-old male patient, who suffers progressive loss of weight and appetite that gradually progressed over the months, in addition to extreme weakness preventing him from performing daily activities, becoming a dependent person of other. Once the functional patterns had been determined, the nursing care plan was created to guarantee good quality care and warmth to the patient; In the same way, once the necessary diagnosis and treatment had been established, the patient's relatives were informed of the pathology, the causes, and the necessary treatment for the patient's well-being, who showed a desire to collaborate.